Risk factors to unfavorable treatment outcomes in patients with drug resistance tuberculosis admitted at a tertiary referral hospital in Rio de Janeiro State (Research, Society and Development, 2022)
This study aims at identifying clinical and demographic factors associated with DR-TB and unfavorable outcomes in a reference TB hospital in Rio de Janeiro State. We performed a retrospective case-control study with presumed DR-TB inpatients hospitalized from 2011 to 2014. DR-TB patients were the case group, and drug-sensitive (DS)-TB, the control group. Logistic regressions were performed to analyze the risk factors associated with DR-TB and the outcomes. Among 135 patients, DR was detected in 41.5%. Being an illegal drug user and having previous TB treatment were associated with DR-TB. Being Afro-Brazilian, male, and under 40 years old were associated with unfavorable outcomes. Patients with rifampicin and isoniazid resistance had 9.7-fold higher odds to death. In conclusion, the high proportion of patients with resistance detected in a tertiary hospital and the poor general condition point to failures in the primary health care that contribute to the proportion of unfavorable outcome.